Quality of Life and Effecting Factors in Patients Undergoing Dialysis: A Comparative Study - Chinnoros, Somporn; Depanya, Chutima (Journal of health and health management, 2020)
This descriptive research aimed to study quality of life and effecting factors in patients undergoing dialysis: a comparative study. The samples were 50 and 40 patients receiving hemodialysis and peritoneal dialysis at a hospital in Bangkok respectively. The research instruments consist of personal data record form, laboratory record form, and Kidney Disease Quality of life Short Form TM Questionnaire (KDQOL-SFTM) version 1.3 with reliability .90. Data were collected from April to June 2019, data were analyzed using statistic distribution, frequency, percentage, mean, standard deviation, Multiple regression analysis, t-test and F-test. The finding revealed that patients receiving hemodialysis versus patients receiving peritoneal dialysis showed no differences in overall quality of life. When considering each aspect, it was found that the patients undergoing hemodialysis versus the peritoneal dialysis patients had the following criteria. The mental component summary was significantly different at the .01 level, while other aspects were not different. When comparing the quality of life of patients by sex and marital status, it was found that both groups of patients with different sexes had no differences in overall quality of life and in each aspect. Patients undergoing hemodialysis with different marital status had statistically different quality of life at the .05 level. Factors affecting quality of life of patients receiving hemodialysis were age, blood albumin levels and adequacy of hemodialysis. At the .05 level, the three variables were able to predict variations in quality. The physical component summary of patients receiving hemodialysis was 42% (R2 = 0.42), while the variables did not affect overall quality of life and other aspects.